'Please wear mask!' Covid-19 in the translation landscape of Thessaloniki: a cross-disciplinary approach to the English translations of Greek public notices. (3rd July 2022) - Lees, Christopher
ABSTRACT: This paper examines the English translations of Greek Covid-19 notices in the city of Thessaloniki which either inform the public about the precautions necessary to avoid infection with Covid-19, how the pandemic has affected the running of a particular service or business or how a business can help with the pandemic. Ιt combines methods from linguistic landscape research, sociolinguistics, and the sociology of translation, in order to examine how business people and employees have translated notices from Greek into English with the aim of communicating information with non Greek-speaking visitors to the city in relation to the pandemic. The qualitative data that will be presented here include translated notices from local businesses and state-run services. The data and analysis show that these particular translations are typically carried out by non-professional translators with varying degrees of competence in English, who rely on their existing linguistic resources to achieve their communicative goals.